El teatro infantil para desarrollar la autoestima de los niños de preparatoria de la unidad educativa Dr. Reinaldo Espinoza Aguilar del barrio Chontacruz de la ciudad de Loja, periodo 2019-2020 - Ordóñez Túqueres, Ana Gabriela (2020)
The research entitled THE CHILDREN'S THEATER TO DEVELOP THE SELF-ESTEEM OF HIGH SCHOOL CHILDREN OF THE EDUCATIONAL UNIT “DR. REINALDO ESPINOZA AGUILAR” FROM THE CHONTACRUZ NEIGHBORHOOD OF THE CITY OF LOJA, PERIOD 2019-2020; the general objective was to determine the incidence of children's theater in the development of the self-esteem of high school children. Regarding the literature review, topics related to children's theater and self-esteem were addressed; in the development of the investigation the methods used were: scientific, analytical - synthetic, inductive - deductive, statistical - descriptive, dialectical and hermeneutical; In order to obtain information, the high school teacher was interviewed and the Lewis Aiken Self-Esteem Test was applied to the children, which allowed diagnosing the low level of self-esteem in the children. The investigated population comprised 1 teacher and 32 children. The results reflect that the population has two types of diagnosis: 53% of children had an unsatisfactory and unsatisfying level, that is to say a development of their low self-esteem difficulties in socializing with peers; being aggressive, shy and insolated. Finally, 47% of infants showed a high level of self-esteem. Redarding the proposal, 94% of children adquired skills to develop high self-esteem, while the remaining 6 % is in process, while, children who where at a high self-esteem level whit 47% now increased to 94%. Concluding that the alternative proposal based on children´s theatre was effective in developing the self-esteem of the children investigated when assessing it and the impact of this was evident, corroborating whit the data obtained in the results of the application of the pre-test and post-test. Children went from having unsatisfactory, unsatisfying levels of self-esteem (low self-Esteem) to satisfying and very satisfying (high self-esteem).